2023
DOI: 10.1002/ecs2.4439
|View full text |Cite
|
Sign up to set email alerts
|

Estimating recruitment rate and population dynamics at a migratory stopover site using an integrated population model

Abstract: Consideration of the full annual cycle population dynamics can provide useful insight for conservation efforts, but collecting data needed to estimate demographic parameters is often logistically difficult. For species that breed in remote areas, monitoring is often conducted during migratory stopover or at nonbreeding sites, and the recruitment rate of new breeding adults can be difficult to estimate directly. Here, we present an integrated population model that uses mark-resight and count data to estimate su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…islandica) wintering in Great Britain was maintained by alternating trends of survival and recruitment, implicating a potential role of density-dependent processes in population regulation. Knots using Delaware Bay during spring migration experienced consistently high apparent survival which was offset by consistently low recruitment between 2005-2018, resulting in a slightly positive population growth rate (Tucker et al, 2023). Using data from two large shorebird monitoring datasets, Bart et al (2007) suggested the most likely mechanisms of North American shorebird population declines are reduction in breeding population size and poor reproduction, rather than an artifact potentially explicable by shifting distributions.…”
Section: Discussionmentioning
confidence: 99%
“…islandica) wintering in Great Britain was maintained by alternating trends of survival and recruitment, implicating a potential role of density-dependent processes in population regulation. Knots using Delaware Bay during spring migration experienced consistently high apparent survival which was offset by consistently low recruitment between 2005-2018, resulting in a slightly positive population growth rate (Tucker et al, 2023). Using data from two large shorebird monitoring datasets, Bart et al (2007) suggested the most likely mechanisms of North American shorebird population declines are reduction in breeding population size and poor reproduction, rather than an artifact potentially explicable by shifting distributions.…”
Section: Discussionmentioning
confidence: 99%
“…However, modelling methods have advanced to help make the best inference possible from available data through analysis of multiple information sources (Schaub & Kéry, 2022; Anstead et al, 2023). Such methods have been used to combine multiple surveys to estimate horseshoe crab abundance and to combine mark–recapture and aerial counts to estimate the abundance and survival of the horseshoe crab‐reliant red knots in Delaware Bay (Atlantic States Marine Fisheries Commission (ASMFC), 2022a; Tucker et al, 2023). Greater use of these methods could be explored throughout the horseshoe crabs’ range to better prepare for future assessments.…”
Section: Implications For Conservationmentioning
confidence: 99%